-6/5 = 24/x
-6x = 120 {multiply by 5x}
x = -20 {divide by -6}
2006-11-30 07:54:37
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
x = -20 -6 into 24 = -4 times 5 = -20
2006-11-30 07:56:45
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
-6/5 = 24/x
multiply both sides by 5x:
-6x = 5*24
divide both sides by -6:
x = 5*24/-6
multiply by -1/-1:
x = -5*24/6 = -5*4 = -20
2006-11-30 08:02:44
·
answer #3
·
answered by Helmut 7
·
0⤊
0⤋
-6/5 = 24/x
-5/6 = x/24 {invert both sides -- still equal}
-5/6 * 24 = x {multiply both sides by 24}
-5 * 4 = x {cancel out the 6}
-20 = x {mulitply two factors}
x = -20
2006-11-30 07:54:29
·
answer #4
·
answered by Dave 6
·
0⤊
0⤋
Just cross multiply:
-6/5 = 24/x
(multiply each side by both 5 and x.)
-6x = 120
(divide by -6)
x = -20
2006-11-30 07:54:49
·
answer #5
·
answered by TOC 2
·
0⤊
0⤋
x = -20
2006-11-30 07:53:40
·
answer #6
·
answered by j3nzsrfs 1
·
0⤊
0⤋
-6/5 = 24/x
-6x = 120
x = -20
2006-11-30 07:56:06
·
answer #7
·
answered by Fizban 1
·
0⤊
0⤋
x= -20
2006-11-30 07:53:13
·
answer #8
·
answered by M C 3
·
0⤊
0⤋